ÐÐµÐºÐ¾Ñ‚Ð¾Ñ€Ñ‹Ðµ Ð¿Ð¾ÐºÐ°Ð·Ð°Ñ‚ÐµÐ»Ð¸ ÑÐ¸ÑÑ‚ÐµÐ¼Ñ‹ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ð¿Ð¾ÑÐ·Ð° ÐºÑ€Ñ‹Ñ Ð¿Ð¾ÑÐ»Ðµ Ñ‡Ð°ÑÑ‚Ð¸Ñ‡Ð½Ð¾Ð¹ Ð³ÐµÐ¿Ð°Ñ‚ÑÐºÑ‚Ð¾Ð¼Ð¸Ð¸ Ð¸ Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ†Ð¸Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ - Moiseyeva, N. N.; Rozanova, E. D.; Mazur, S. P.; Petrenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2002)
The authors studied the content of fetal and total hemoglobin in blood of rats after 70%-hepatectomy and transplantation of cryopreserved human embryonic liver (HEL) cells. Partial hepatectomy leads to a decrease in the content of total hemoglobin in rats’ blood during experiment and increasing of fetal hemoglobin level by the 3rd day. After transplantation of cryopreserved HEL cells the content of total hemoglobin markedly exceeds the results in partially hepatectomised rats without transplantation by the 1st and 2nd day, and the level of fetal hemoglobin during this period decreased in 1.5 times. The transplant was identified in histological sections of liver and spleen from partially hepatoectomised rats with the method of fluorescent microscopy using monoclonal antibodies, labelled with fluorescent dye CD45-FITC.